Victory Celebrations - London, 1946 (1946)
1946 1945-1960 "Victory Celebrations - London, 1946" [HFR0128], 1946 Official programme of the Victory Celebrations on 8 June, 1946. During the day, mechanised vehicles and marching columns paraded through London and there were fly-pasts by war planes. Musical and theatrical entertainments and children's activities were organised in all the central London parks. In the evening, there was open-air dancing, floodlighting of public buildings and ships on the Thames, and firework displays. Marching columns included Home Front workers as well as the armed forces.